Oncology nursing care standards - A.M. de Kleijn; M.E. Muller (AOSIS, 1991)
Oncology nursing as a specialised nursing discipline has no published nursing care standards for South Africa. The purpose of this study was to formulate oncology nursing standards for a particular research hospital A specific approach was used and the oncology nursing experts in the research hospital compiled and formulated the standards. Group discussions and critical debating of the standards followed. The standards were ratified by means of verbal consensus between the experts and professional nurses in the oncology unit. These standards could serve as a guide to ensure quality oncology nursing care. National validation of the standards is recommended